2002
DOI: 10.1021/ja021073g
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium of Formation of the 6-Carbanion of UMP, a Potential Intermediate in the Action of OMP Decarboxylase

Abstract: There has been some speculation that the C-6 position in UMP may be unusually acidic, stabilizing a carbanion that is generated at this position during OMP decarboxylation. On the basis of the rate of OH- catalyzed deuterium exchange at elevated temperatures we estimate that the pKa value for ionization at C-6 of dimethyl uracil is 34 +/- 2 in water. The same method yields a value of 37 +/- 2 for ionization at C-2 of thiophene in good agreement with the value determined by polarographic methods. The barrier to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
65
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 19 publications
(36 reference statements)
1
65
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12] Most of the studies involve the investigation of the nature and stability of the intermediate. As shown in Scheme 1, acid 1 decarboxylates at elevated temperatures to give 1,3-dimethyluracil (2) as the sole product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12] Most of the studies involve the investigation of the nature and stability of the intermediate. As shown in Scheme 1, acid 1 decarboxylates at elevated temperatures to give 1,3-dimethyluracil (2) as the sole product.…”
Section: Introductionmentioning
confidence: 99%
“…A rate constant of 10 11 s −1 was employed for the reaction between the carbanion and water, k HOH , as in the case of uracil 2. 8 The pK a values of the 6-CH groups of both pyridones 6 and 7 are thus estimated to be 32 ± 2, using equation 1.(1) …”
mentioning
confidence: 99%
“…This result has further demonstrated that there is a lack of correlation between the stability of the carbanion and the rate of the decarboxylation (see Table 1). However, the values from two separate studies on uracil 4 do not agree with each other very well [12,13]. The two studies were carried out using the same kinetic method but under somewhat different conditions due to the chemical reactivity of 4 [13].…”
Section: Resultsmentioning
confidence: 93%
“…The pK a values of the 6-CH groups of compounds 4-6 in water were determined in order to estimate the stability of carbanions 7-9 in aqueous medium [12,13]. Unfortunately, the pK a values determined for uracil 4 in two separate studies were not consistent as shown in Table 1 [12,13]. In this study, we report the estimated pK a values determined in DMSO, a solvent with similar properties to that employed in kinetic measurement of the decarboxylation reactions, sulfolane.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, when pyridones 5 and 6 were treated under the same conditions, no proton-deuterium exchange was observed, indicating that carbanions 8 and 9 are less stable than carbanion 7 . The rates of proton-deuterium exchange were eventually determined over the temperature range of 80–110 °C in 1 N NaOD/D 2 O and the results are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 97%